Molecular characterization of ESBL producing uropathogenic Escherichia coli. - Thapa, Garima (2021)
ABSTRACT: Background: Antibiotic resistance is a globally disappointing trend and challenging problem for researchers of all fields worldwide. Health and economic burdens are two factors provoked due to antibiotic resistance, and today's world is entering the same era. Both phenotypic and genotypic characterizations would be required to understand the molecular mechanisms generating resistance and their pathological consequences. The major goal of this study was to see how common the blaTEM and blacTX-M genes were in extended spectrum β=lactamase (ESBL) producing E. coli isolates. Methodology: The E. coli isolated from urine samples of Urinary Tract Infection (UTI) diagnosed patients between October 2020 to August 2021 at Meridian Health Care Center and Abhiyan Pathology Lab were collected and included in this study. On the basis of colony appearance and biochemical characteristics, bacterial isolates were identified. The modified Kirby-Bauer disk diffusion method was used to screen clinical isolates for antimicrobial susceptibility testing (AST), while a combination disk diffusion method was used to identify ESBL producers. The ESBL genes blaTEM and blacts-M were detected using standard polymerase chain reaction (PCR) in ESBL positive isolates. Results: After performing antibiotics susceptibility testing and phenotypic confirmatory tests of 54 isolates of E. Coli, we identifies a large frequency of multi-drug resistance and extended spectrum beta-lactamases producers, 57.4% and 46.3%, respectively. Similarly, the CTX-M gene was found to be more prevalent than the TEM gene following PCR amplification, with 72% and 56% occurrences, respectively. Conclusion: Multi drug resistance (MDR) bacteria made up half of the isolates in our investigation. To maximize treatment and minimize antibiotic resistance, routine identification of and infecting pathogen followed by AST is crucial. Key Words: Antibiotic resistance, Escherichia coli, Extended-spectrum β-lactamase.